Upaya Meningkatkan Minat Membaca Melalui Metode Sustained Silent Reading pada Siswa Kelas IV SDN 5 Keresek - Wulandari, Widya; Aljamaliah, Syifa Nailul Muna; Kurniawati, Kurniawati (Didaktika, 2022)
Reading is one of the most important skills in the language. Before someone has writing skills, they should have reading skills first. However, let alone being skilled, growing interest in reading itself is still quite difficult.   Literacy culture cannot be found in most schools in Indonesia, including in SDN 5 Keresek. The application of the SSR (Sustained Silent Reading) method in several studies can overcome the problem of reading.  Therefore, this study aims to find out whether the SSR (Sustained Silent Reading) method can increase the reading interest of students of grade IV SDN 5 Keresek. The research approach that is used is qualitative with case study methods. Based on the results of the study, it can be concluded that the SSR (Sustained Silent Reading) method effectively increases the reading interest of students of grade IV SDN 5 Keresek in Garut Regency. This increase is seen gradually in the observation of the first cycle and the second cycle.  The increase in reading interest in each of these cycles can occur because sustained silent reading helps encourage students to focus on following reading activities with books that have been handpicked by them. With this method, students are not easily distracted because everyone reads their book quietly and calmly.